Legal Analysis of Default in Oral Lease Agreement (Case Study of Supreme Court Decision No. 2368 K/Pdt/2019) - Dantjie, Angel Heraria; Surahmad, Surahmad (Jurnal Daulat Hukum, 2025)
Agreements are one of the main sources of civil legal relations in Indonesia. In practice, agreements are not always stated in written form, but are often made orally. This raises legal issues when a breach of contract occurs and the injured party files a lawsuit in court. This journal discusses the Supreme Court Decision No. 2368 K/Pdt/2019 between Flavianus Fexa versus Cau Phen as a concrete example of the validity of oral agreements and their proof in civil procedural law. The analysis focuses on the application of Articles 1320, 1234, and 1238 of the Civil Code and the Supreme Court's considerations in declaring the defendant in breach of contract. Although the plaintiff's lawsuit was rejected at the District Court and High Court levels due to the absence of written evidence, the Supreme Court granted the cassation by emphasizing the importance of substantial justice and the validity of proof through other evidence such as witnesses and summons letters. This decision confirms that oral agreements remain valid as long as they meet the elements of an agreement, have a clear object, and can be proven. In addition, this decision can also be an important precedent in the practice of Indonesian civil law, considering that many people still make agreements verbally. The conclusion of this Journal emphasizes the importance of legal protection for oral agreements and the flexibility of judges in upholding substantive justice compared to mere procedural formalities.